Vena cava balloon occlusion for pulmonary embolism prevention during resection of giant uterus fibroids. Issue 5 (25th May 2022) - Kotsis, Thomas; Christoforou, Panagitsa; Chatziioannou, Achilles; Memos, Nikolaos; Theodoraki, Kassiani; Konstadoulakis, Manousos
Abstract: We report the case of a single 46-year-old woman presenting with huge uterine fibroids growing for the last 12 years, resulting in a recent common iliac vein thrombosis. Due to the high risk for pulmonary embolism, an occluding balloon was inserted through the right jugular vein before the abdominal incision and occluded the vena cava just inferior to the renal veins. The tumor was easily mobilized, and the vena cava bifurcation was exposed and controlled until the uterus with the masses was resected. We recommend this method for oncovascular surgeries involving deep vein thrombosis and vein thromboembolism.